1998
DOI: 10.1161/01.atv.18.8.1350
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Increases and Interferon-γ Decreases Expression of CD36 in Human Monocyte–Derived Macrophages

Abstract: Abstract-CD36 is a glycoprotein with an M r of 88 kDa that is expressed on platelets, monocytes/macrophages, capillary endothelial cells, and adipocytes. We previously demonstrated that CD36 is involved in the uptake of oxidized low density lipoprotein (OxLDL) by using CD36-deficient macrophages (J Clin Invest. 1995;96:1859). However, the regulation of CD36 expression in human monocyte-derived macrophages has not been fully elucidated. The current study attempted to clarify the effect of OxLDL and cytokines, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 41 publications
7
45
0
Order By: Relevance
“…Reports using the human monocyte cell line THP-1 indicate that IFNγ and the transcription factor that it signals through, STAT1, are responsible for increased foam cell formation and CD36 expression [42,43]. By contrast, similar studies performed using primary human MDMs however are in agreement with our own [44][45][46]. Geng and Hansson, for example, found that IFNγ caused a reduction in acetylated LDL cellular association and cholesterol accumulation [44].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Reports using the human monocyte cell line THP-1 indicate that IFNγ and the transcription factor that it signals through, STAT1, are responsible for increased foam cell formation and CD36 expression [42,43]. By contrast, similar studies performed using primary human MDMs however are in agreement with our own [44][45][46]. Geng and Hansson, for example, found that IFNγ caused a reduction in acetylated LDL cellular association and cholesterol accumulation [44].…”
Section: Discussionsupporting
confidence: 86%
“…Geng and Hansson, for example, found that IFNγ caused a reduction in acetylated LDL cellular association and cholesterol accumulation [44]. Likewise, Nakagawa et al found that IFNγ caused a decrease in CD36 expression in primary human MDMs [45]. A recent publication by Oh et al using human MDMs from diabetic patients treated with IFNγ and LPS showed reduced cholesterol accumulation when compared with alternatively activated macrophages [46].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2002) reported that the p38 MAP kinase pathway may also affect PPAR-γ activation and induction of CD36 gene expression. The role of interferon-γ in CD36 regulation remains controversial, although in our hands, we observed no effect (Nakagawa, et al, 1998,Zuckerman, Panousis, Mizrahi, & Evans, 2000. As mentioned previously, CD36 interaction with apoptotic cells can lead to IL-10 secretion, and Rubic and Lorenz (2006) have reported that IL-10 decreases CD36 expression.…”
Section: Cd36 Regulationsupporting
confidence: 45%
“…IL-4, a Th2 cytokine, has been shown to increase monocyte/Mu expression of CD36 [17], whereas expression of CD36 is down-regulated in response to a Th1 cytokine like IFN-c [32] and to LPS or dexamethasone [17].…”
Section: Discussionmentioning
confidence: 99%